The Transformation of Social Work Education Through Virtual Learning - Maiden, R. Paul (Newcastle upon Tyne, UK : Cambridge Scholars Publisher, 2019)
Over the past few years, numerous highly ranked, Tier 1 universities across the United States have embraced the development of advanced online degrees, a niche of secondary education long held by a small group of private, for-profit universities. Rapid advances in online learning technology, increasingly sophisticated, and easy to use 'learning management systems' and 'anytime, anywhere access' has dramatically increase the demand of individuals, mostly full time employed, working professionals. This volume addresses the dramatic changes that are occurring in social work pedagogy as more schoo.
Developing and sustaining an online community of practice in social work education / Smith-Maddox, Renee; Kratz, Stacy; Wiley, June -- From aspiration to action: advocacy and innovation practice for social justice in online social work education / Enrile, Annalisa; Smith-Maddox, Renee -- The Person-in-the-virtual-environment: building a diverse, engaged and collaborative virtual faculty / Schwartz, Sara L.; Wiley, June L. -- Collaborative learning: laying the pedagogical foundation for design and development of health and integrated care policy courses in the virtual learning environment / Joosten-Hagye, Dawn -- Instilling empathy in the virtual learning environment / Araque, Juan Carlos; Zaleski, Kristen -- Designing a virtual DSW education around the grand challenges: the USC model / Abel, Eileen M.; Maiden, R. Paul; Rank, Michael -- Clinical practice skill acquisition in a virtual learning environment / Harper, Bianca; Lewis, Jennifer -- Virtual positivity: positive psychology practice increases performance, engagement and well-being / Blair, Sherry -- When the past is present in the classroom: utilizing a trauma-informed approach in the virtual setting / Baron, Mary Walker; Brown, Danielle; Cardinal, Laura; Hess, Susan; Singh, Melissa Indera -- Being who you are makes you a change agent: making inclusive space for growth during hard times / Thomas, Shane'a -- Field education in a virtual environment. From zero to 7,000: creating a social work field placement program from the ground up to the clouds / Cox, Tory; Hsiao, Suh Chen; Pringle-Hornsby, Elizabeth -- The Use of simulation experiences to develop practice skills: a quantum leap in field education / Wood, Gary; Phillips, Betsy -- Cultivating relationships with agency field instructors: collaborators in virtual learning / Doyle, Kerry; Parga, Jen; Wobbe-Veit, Lisa -- From remediation to success: helping students turn it around in field practicum / Cislowski, Ruth; Ford, Amber; Lee, Terri; Michelsen, Renee.
Includes bibliographical references.
Print version record.
eBooks on EBSCOhost
Keywords: Social work education -- United States; Social service -- Web-based instruction; Distance education -- United States; Service social -- Étude et enseignement -- États-Unis.; Enseignement à distance -- États-Unis.; Distance education; Social work education; United States